The Protection of Human Life: A Survey of the Qur'an and the Sunnah - Dr. Khadija Aziz,; Dr. Hashmat Begum,; Miss Maryam Hamid,; Miss Hafsa,; Dr Nargis, (Al-Qanṭara, 2024)
This research paper provides a comprehensive exploration of the profound importance placed on the sanctity of human life within Islamic teachings, as derived from the Qur'an and the Sunnah. The study underscores the emphasis Islam places on the protection, preservation, and respect for human life as a foundational principle in its doctrine. Through a detailed analysis of key Qur'anic verses and prophetic traditions, the paper examines the ethical, moral, and practical implications of these teachings in multiple spheres of human life. These include areas such as medical ethics, where the protection of life takes precedence, social justice, which emphasizes fairness and the welfare of all individuals, conflict resolution, advocating for peace and the sanctity of human life even in times of war, and environmental stewardship, which promotes the preservation of life by caring for the planet. The research sheds light on how these principles shape Islamic perspectives on contemporary global issues and their relevance in today's complex world.